2006
DOI: 10.1007/s11099-006-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition and xanthophyll cycle activity in bayberry (Myrica rubra) leaves induced by high irradiance

Abstract: The effect of high irradiance (HI, photosynthetically active photon flux density of 1 300 μmol m −2 s −1 ) on net photosynthetic rate (P N ), chlorophyll fluorescence parameters, and xanthophyll cycle components were studied in fruit tree bayberry leaves. HI induced the photoinhibition and inactivation of photosystem 2 (PS2) reaction centres (RCs), which was characterized by decreased P N , maximum yield of fluorescence after dark adaptation (F m ), photochemical efficiency of PS2 (F v /F m ) and quantum yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
(42 reference statements)
3
18
0
Order By: Relevance
“…In the present study, this parameter was the most representative of the effect of high irradiance stress. Similar observations have also been reported by Guo et al (2006) in bayberry plants subjected to high irradiance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, this parameter was the most representative of the effect of high irradiance stress. Similar observations have also been reported by Guo et al (2006) in bayberry plants subjected to high irradiance.…”
Section: Discussionsupporting
confidence: 90%
“…According to Guo et al (2006), photoinhibition in higher plants occurs when plants experience irradiance at or above the level that is saturating for growth. The lower photosynthetic rate observed in O-plants could be ascribed to partial photoinhibition.…”
Section: Discussionmentioning
confidence: 99%
“…But for the photosynthetic organisms in BSCs, they have no stomata except for a few liverworts and mosses (Wu 1992). Meanwhile, some studies also reported that the midday depression of photosynthetic efficiency coincided with the higher PAR and photoinhibition (Guo et al 2006;Huang et al 2006). Therefore, we speculate that PAR may play a significant role during the course of diurnal changes of photosynthetic efficiency in BSCs.…”
mentioning
confidence: 64%
“…Plants grown at low PPFD have low photosynthetic capacity and a low CO 2 assimilation rate. In contrast, an environment with high irradiance can negatively affect photosystem II (PSII) and photosynthesis declines (Guo, Guo, Zhou, Hu, & Shen, 2006).…”
Section: Morfoanatomia E Fisiologia De Plântulas De Pouteria Gardnerianamentioning
confidence: 99%